The process of the world building of "Built to Scale" - Sek, Qin Yi (Nanyang Technological University, 2023)
As the Art Director of Built To Scale, I strived to build the world of Paper Architects Co. to be as original and as believable as it could be. Some considerations to achieve this includes thinking of the company’s brand image, the office’s image, and understanding an architecture firm’s office hierarchy and politics.